2017
DOI: 10.1016/j.aogh.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Money Gone Up in Smoke: The Tobacco Use and Malnutrition Nexus in Bangladesh

Abstract: BACKGROUND The tobacco epidemic in Bangladesh is pervasive. Expenditures on tobacco may reduce money available for food in a country with a high malnutrition rate. OBJECTIVES The aims of the study are to quantify the opportunity costs of tobacco expenditure in terms of nutrition (ie, food energy) forgone and the potential improvements in the household level food-energy status if the money spent on tobacco were diverted for food consumption. METHOD We analyzed data from the 2010 Bangladesh Household Income … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 13 publications
1
10
0
2
Order By: Relevance
“…On average, a tobacco-user household spent nearly 392 Bangladesh Taka (BDT) per month in 2010, constituting 4.1% of the household budget. This expenditure share is much higher than many other food consumption items, including fruits, legumes and beans, oil and fat, milk, sugar, and eggs [ 20 ]. Husain et al [ 20 ] suggested that, in Bangladesh, the tobacco expenditure-shift could translate to an additional 4.6 to 7.7 million food-energy malnourished persons meeting their caloric requirements.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On average, a tobacco-user household spent nearly 392 Bangladesh Taka (BDT) per month in 2010, constituting 4.1% of the household budget. This expenditure share is much higher than many other food consumption items, including fruits, legumes and beans, oil and fat, milk, sugar, and eggs [ 20 ]. Husain et al [ 20 ] suggested that, in Bangladesh, the tobacco expenditure-shift could translate to an additional 4.6 to 7.7 million food-energy malnourished persons meeting their caloric requirements.…”
Section: Introductionmentioning
confidence: 99%
“…This expenditure share is much higher than many other food consumption items, including fruits, legumes and beans, oil and fat, milk, sugar, and eggs [ 20 ]. Husain et al [ 20 ] suggested that, in Bangladesh, the tobacco expenditure-shift could translate to an additional 4.6 to 7.7 million food-energy malnourished persons meeting their caloric requirements. Previously, Efroymson et al [ 8 ] asserted that, in Bangladesh, the average male cigarette smoker spends more than twice as much on cigarettes as compared to combined expenditures on clothing, housing, health and education; that a typical poor smoker could add over 500 calories to the diet of one or two children by eliminating daily tobacco expenditure; and that an estimated 10.5 million malnourished people could have an adequate diet if money on tobacco were spent on food instead.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results provide support for the conclusion that households that purchase tobacco may be diverting funds that would otherwise be spent on more costly food items, such as milk, and replacing those calories with inexpensive cereal grains 12 . A separate analysis of this dataset found that within food consumption categories, cereals constituted the largest share of expenditure (>40% of total food expenditure) among tobacco-use households 9 . Husain et al 18 recently (2018) reported that household consumption of tobacco competes with other household expenditures; while tobacco-use households spent more on food and medical items, compared with non-use households, they spent less on clothing, housing, education, transportation, and communication.…”
Section: Discussionmentioning
confidence: 99%
“…Less is known about the relationship between tobacco use, especially smokeless tobacco use, and dietary patterns among populations in developing countries. In a low-income setting, limited resources may result in money being diverted from basic necessities, including food, to tobacco purchasing thus reducing dietary quality and contributing to malnutrition 9 . Combating malnutrition in developing countries is a major global public health priority; expenditure on tobacco has been shown to exacerbate poverty and malnutrition by competing for the limited resources 10 - 12 .…”
Section: Introductionmentioning
confidence: 99%